Women directors and CEO excessive compensation - Khalid Waleed; Muhammad Abubakkar Siddique; Umaal Ahmed Khan; Jam Zia ul Hassan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2021)
This study aims to explore the crucial question whether the presence of female directors on the compensation committees limits the CEO excessive compensation in China or not? To draw the inferences, we use the data of Chinese listed firms for the year 2006 to 2015 and estimate ordinary least square regression as a baseline methodology along with two-stage least squares regression to control the endogeneity issues. We find reliable evidence that Chinese CEOs do receive some excessive compensation which can be mitigated by having gender diverse compensation committee. We also find CEO excessive compensation is positively linked to firm performance when firms have gender diverse compensation committees. Moreover, we also find that the governance role of gender diverse compensation committee on CEO's excessive pay varies across sub-national institutional contingencies.
Keywords: 330; female directors; compensation committee's limits; gender diversecompensation committee; sub-national institutional contingencies